A survey of the literature on airline crew scheduling. (September 2018) - Deveci, Muhammet; Demirel, Nihan Çetin
Abstract: As the airline industry is ever expanding, companies are increasing their fleet sizes to obtain greater market shares. Moreover, as the airlines seek more growth, the complexity and size of the airline crew scheduling problem, which is one of the major planning problems in the industry, is also increasing. For this reason, companies dedicate resources to solve this problem, and lease software at great expense from external sources. Rigorous mathematical models and algorithms are used in solving these problems. This paper presents a survey of airline crew scheduling problems, and their proposed solutions from the literature. As a conclusion, prospective studies will be proposed and discussed with the aim of developing better solutions for airline crew scheduling problems in the future. Graphical abstract: Highlights: Crew scheduling problem in Airline. Different approaches are surveyed, and the solution methodology for the airline crew scheduling problem is discussed. The strengths and weaknesses of these solution methods are provided. Future suggestions and research directions are discussed.